2018
DOI: 10.1111/jgs.15432
|View full text |Cite
|
Sign up to set email alerts
|

Association Between History of Abuse and Falling in Older Adults

Abstract: History of abuse (emotional, physical, or sexual) was strongly associated with falling in older adults living in Bogota. Further research is needed to confirm these findings and further delineate the independent effects of elder abuse on fall risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
7
0
2
Order By: Relevance
“…To the Editor : We agree with Dr. Subedi's letter to the editor that physical activity is an important topic in falls prevention and management, and we did not formally address it in our article on the association between a history of abuse and falling …”
Section: Correlations (Spearman) With Low Physical Activity Bogota mentioning
confidence: 99%
“…To the Editor : We agree with Dr. Subedi's letter to the editor that physical activity is an important topic in falls prevention and management, and we did not formally address it in our article on the association between a history of abuse and falling …”
Section: Correlations (Spearman) With Low Physical Activity Bogota mentioning
confidence: 99%
“…In addition to mortality, evidence also suggests that elder mistreatment is associated with hospitalization and nursing home placement, which can lead to premature death (Dong & Simon, 2013a, 2013b; Yunus et al, 2019). Some physical symptoms were found to be more prevalent among elder abuse victims, such as a higher falls rate, hypertension, pain, activities of daily living and functional impairment, nutritional concerns (such as weight loss, limited food access, lower levels of folate and vitamin D), urinary incontinence and sensory impairment including hearing and vision (Ernst & Smith, 2011; Fang et al, 2018; Heath et al, 2005; Lachs et al, 1997; Reyes‐Ortiz et al, 2018; Smith et al, 2006). Self‐neglect was also found to be associated with lower level of physical function, increased rates of hospitalization, longer length of hospital stay, more frequent use of hospice but shorter time between admission and death (Dong, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Two studies on falling and injurious falling using SABE Ecuador did not explore the link of abuse with falling (Orces, 2013, 2014). To the best of our knowledge, there is only one previous study reporting the association between a history of emotional, physical, or sexual abuse and falling in older adults (Reyes-Ortiz et al, 2018). We believe that recurrent falling can be a consequence of polyvictimization.…”
Section: Introductionmentioning
confidence: 99%
“…In Latin American populations, there is a high prevalence of violence against older adults that may be explained by cultural factors (e.g., violence against women, ageism) and/or historical reasons (Cano et al, 2016; Curcio et al, 2019; Paiva & Tavares, 2015; Piña-Escudero et al, 2019; Sagot, 2005). In the city of Bogota, 34% of older adults had ever experienced at least one type of abuse caused by family or nonfamily perpetrators (Reyes-Ortiz et al, 2018), while across the country of Colombia, 15% of older adults reported some type of abuse caused by family members during the previous 3 months (Curcio et al, 2019). Since the last couple of decades, Ecuador has continued a trend of demographic transition, with a low fecundity rate, an increased proportion of older adults, and increased life expectancy (Daichman & Giraldo, 2013).…”
Section: Introductionmentioning
confidence: 99%